The phylogenetic placement of a new species of Belemia in Nyctaginaceae, and the first plastome description for the genus. Issue 4 (18th May 2020) - Zappi, Daniela C.; Vasconcelos, Santelmo; Watanabe, Maurício T. C.; Oliveira, Guilherme; Oliveira, Renato R. M.; Pires, Eder S.; Harley, Raymond M.; Giulietti, Ana Maria
Abstract : Investigations following the discovery of an unusual new collection from the Amazon lead to a phylogenetic investigation in order to ascertain its position within the Nyctaginaceae. Two different approaches were used: gene trees from nucleotide sequences of ndh F and ITS aiming to check the phylogenetic position of the new species in the genus Belemia (Nyctaginaceae), using mostly the available data; and a phylogenomic analysis based on full plastome sequences of Caryophyllales and related orders. Following that, a description of the new species, Belemia cordata Harley & Giul., complete with illustrations, comments and conservation status are provided. Distinct from B. fucsioides, the only other species of the genus, the new species has branches and flowers covered in multicellular glandular trichomes, leaves with cordate base, inflorescences in congested cymes and included stamens. The species is classified as Critically Endangered as it has been found in a single location and subsequent expeditions to locate the plant were not successful. The second description of the chloroplast genome of Nyctaginaceae is also provided.